hCG promotes secondary ovulation and supplementary corpus luteum formation during early pregnancy in mares - Diego Guedes Campos; Reno Roldi Araujo; Isabela Syllos; Suzana Rossato Feltrin; Isadora Machado Pereira; Fernanda de Souza Rosa; Carolina dos Santos Amaral; Valério Marques Portela; Alfredo Quites Antoniazzi (Theriogenology, 2026)

Endocrine and uterine hemodynamic differences between intra- and interspecific equine pregnancies during early gestation - Diego Guedes Campos; Isabela Syllos Campos; Paulo Henrique Hümmelgen Silva; Beatriz Bringel; Robert H. Douglas; Aline Emerim Pinna; Julio Cesar Ferraz Jacob; Valério Marques Portela; Carolina dos Santos Amaral; Alfredo Quites Antoniazzi (Veterinary Research Communications, 2026)
Interspecific equine pregnancies (mare x donkey) are associated with altered endocrine patterns and increased pregnancy loss; however, the relationship between hormonal dynamics, luteal activity, and uterine hemodynamics in relation to conceptus origin remains incompletely understood. This study aimed to evaluate the influence of conceptus origin on endocrine profiles, supplementary corpora lutea (SCL) formation, and uterine hemodynamics, and to investigate the relationships among these variables. Twenty mares were initially included; however, six were excluded due to pregnancy loss or incomplete follow-up, resulting in a final sample of 14 mares (six stallion-derived and eight donkey-derived pregnancies). Serum progesterone (P4), equine chorionic gonadotropin (eCG), SCL number, and uterine artery Doppler indices, including pulsatility index (PI) and resistivity index (RI), were evaluated at Days 49, 63, 84, and 98 of gestation. Donkey-derived pregnancies showed significantly lower P4 and eCG concentrations, reduced SCL formation, and lower uterine PI and RI compared to stallion-derived pregnancies ( p r = 0.846; p r = 0.733; p = 0.015). All pregnancies were maintained to term. These findings indicate that conceptus origin is associated with distinct endocrine and uterine hemodynamic patterns, supporting integrated hormonal–vascular adaptations in equine pregnancy.

Ezrin immunoexpression in trophoblast cells of the equine placenta - Isabela Syllos Campos; Bárbara Paula Dos Santos Batista; Ana Carina Heil Silva Matos; Juliana Da Silva Leite; Gustavo Mendes Gomes; Letícia Patrão De Macedo Gomes; Aline Emerim Pinna; Ana Maria Reis Ferreira (Journal of Equine Veterinary Science, 2023)